Pengembangan Model Alat EXPAS (Explosion Power, Agility, Strength) untuk Aktivitas Kebugaran Jasmani Peserta Didik Sekolah Menengah Pertama (Indonesian Journal for Physical Education and Sport, 2021)
The purpose of this study is to implement the development of lerning models of physical fitness aktivities through the EXPAS (Explosion Power, Agility, Strength) tool for Physical education this research is the Research and Development (R & D). The following reserch procedure: 1) the potential and problems, 2) data collection, 3) product design, 4) validation of desaign (1 expert physical education and 2 learning experts), 5) revised desaign, 6) test a small scale (30 learners), 7) revision products, 8) large trial (80 lernears), 9) revision products, 10) which produces a tool of mass-production. The results of the initial product expert. Validation study obtained an averge 80% are very good, with some revisions layer handle for push up and tool section. The results of of the small scale trials obtained an averge of 84% (excellent). The results of the revision of the expert stated that it was very appropriate to use. The results of large-scale trials obtained an averge of 91% (excellent). Based on the analysis of reserch, EXPAS tool ( Explosion Power, Agility, Strength) can be used as a teaching model of physical fitness activities in schools.